Efektivitas Sistem Jaringan Dokumentasi dan Informasi (SJDI) Hukum Di Daerah Istimewa Yogyakarta. Effectiveness of Documentation and Information Network System Law in Daerah Istimewa Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Sekolah Pascasarjana Universitas Gadjah Mada, 2003)
ABSTRACTIn the 21'th century, the information become the need, commodity and strength in the global community. One of them is law information and documentation. To get an access of the law information easily, fast and accurately the Documentation and Information Network System (DINS) was build.This paper describes the implementation of Law Information and Documentation System on Government of Daerah Istimewa Yogyakarta based on the Man Power Capability (X1) technology (X2), organization climate (X3), commitments of group member (X4) and leadership style (X5). The results showed that influence variable of man power capability (X1) has not influenced on significantly to effectiveness, while the other variable technology (X2), organization climate (X3), commitments of group member (X4) and leadership style (X5) have an influence on effectiveness significantly although in the range of low to middle value.Leadership style (X5) of the leader in the Documentation and Information Network System (DINS) unit through analysis by using product moment and multiple linier regression was proved that it has a great influence on the effectiveness so that the effective or not the Documentation and Information Network System (DINS) on Government of DIY depends on the leadership style of the leader.